Constantine, the Hellblazer. Volume 1, Going down - Doyle, Ming; Tynion, James, IV (DC Comics, 2016)
"The dark adventures of DC's foremost occult detective continue in an all-new series as he investigates the cruelest case he's ever come across--his own dark history! Writer Ming Doyle (THE KITCHEN, Quantum and Woody) relaunches John Constantine's solo series with more horrifying roots than ever before"--